Long term survey of body composition in hemodialysis patients using the Body Composition Monitor® (BCM) - Stanislas Trolonge; Philippe Chauveau; Claude Desvergnes; Nicole Larroumet; Christian Combe (The Korean Society of Nephrology, 2012)
Since 2 years all 265 incident patients in self-dialysis units were included in a prospective study. Every 6-months, clinical and biological nutritional evaluation was associated to a BCM measure. 205 pts have a complete set of data at start (age 60±16 years, BMI 25±5 kg/m2, albumin 37±4 g/L, prealbumin 0.32±0.1 g/L, CRP median 5 mg/L), 135 pts at 6 mo and 56 pts at 2 years. Measures were performed before HD session to ensure stability and reproducibility of body fluid compartments by the same examiner. Lean and fat masses (lean tissue index: LTI, fat tissue index: FTI) were normalized by square body height and compared with a reference range derived from 2000 healthy controls, according to gender and age. 28% of pts had values of LTI below the 10th percentile. A linear correlation exists (p<0.001) between pre-dialysis creatinine level and LTI. Albumin or prealbumin were not predictive of sarcopenia. Prescribed post dialysis BW was underestimated in 25% of pts and 16% remain overhydrated. In stable patients repeated measures analysis reveal no significant variation of LTI even in case of reevaluation of BW and gain of BW is associated with fat mass increase. BCM is a simple tool in clinical practice to evaluate body composition and hydratation status and help to guide nutritional support.